EFEKTIVITAS MODEL PEMBELAJARAN POE MATERI ELEKTROLIT/NON-ELEKTROLIT DALAM MENINGKATKAN KEMAMPUAN BERPIKIR EVALUATIF - Windawati Windawati; Ratu Betta Rudibyani; Tasviri Efkar (Universitas Lampung, 2015)
This research was aimed to describe the effectiveness of POE learning model in increasing students the ability of the evaluative thinking on electrolyte and non-electrolyte topics. The population of this research was all first year secondary student in science class of SMA Negeri 1 Sukoharjo. X IPA1 and X IPA 2 classes as a reasearch sample was taken by purposive sampling technique. The Quasi experimental with non equivalent pretest-posttest control group design used as research method. The effectiveness of POE learning model in the learning was showed by the significant n-Gain difference between the experimental class and the control class. The result showed that n-Gain average of the evaluative thinking ability in control class was 0,38 and 0,66 for experiment class. Based on these results, it can be concluded that POE learning model was effective in increase the ability of the evaluative thinking on electrolyte and non-electrolyte topics.Penelitian ini bertujuan untuk mendeskripsikan efektivitas model pembelajaran POE dalam meningkatkan kemampuan berpikir evaluatif siswa pada materi larutan elektrolit dan non-elektrolit. Populasi dalam penelitian ini adalah seluruh siswa kelas X IPA SMA Negeri 1 Sukoharjo. Sampel dalam penelitian ini adalah siswa kelas X IPA 1 dan X IPA 2 yang diambil melalui teknik purposive sampling. Metode penelitian ini adalah kuasi eksperimen dengan Non Equivalence Pretest-Postest Control Group Design. Efektivitas model pembelajaran POE dalam pembelajaran ini ditunjukkan oleh perbedaan n-Gain yang signifikan antara kelas kontrol dan kelas eksperimen. Hasil penelitian menunjukkan rata-rata n-Gain keterampilan brpikir evaluatif kelas kontrol adalah 0,38 dan 0,66 untuk kelas eksperimen. Berdasarkan hasil tersebut dapat disimpulkan bahwa model pembelajaran POE efektif dalam meningkatkan keterampilan berpikir evaluatif pada materi larutan elektrolit dan non-elektrolit.Kata kunci: elektrolit/non-elektrolit, kemampuan berpikir evaluatif, model pembelajaran POE.